Impact of SOP Implementation, Training, and Employee Satisfaction on Service Quality - Belinda, Jane; Lukito, Patricia Michelle; Hidayat, Mathilda Angelina (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2025)
High-quality administrative services are an essential component of the healthcare system, especially in healthcare facilities such as the Pelita Sehat Clinic in Bogor. Inadequate administrative services can hinder the overall effectiveness of service delivery and potentially affect patient satisfaction and operational efficiency. This study explores how the implementation of Standard Operating Procedures (SOP), employee training, and employee satisfaction influence the quality of administrative services. These three elements are widely recognized in organizational studies as key drivers of performance excellence. The research employs a quantitative approach with a causal design and utilizes survey methods to gather insights from individuals directly involved in administrative functions. Data were collected using a Likert-scale questionnaire, which was designed to measure perceptions, experiences, and levels of satisfaction related to administrative tasks. The analysis was conducted using structural equation modeling, which allows for the simultaneous assessment of multiple influencing factors. The results show that the application of SOPs, the provision of employee training, and the level of employee satisfaction each have a significant impact on improving the quality of administrative services. These factors collectively contribute to better service consistency, responsiveness, and staff accountability. The study highlights that a substantial portion of service quality variation can be explained by these three variables. The novelty of this research lies in its integrated assessment of these elements within a unified model specific to clinical services. From a managerial perspective, clinic leaders are advised to regularly audit SOPs, provide continuous skill development opportunities, and establish incentive systems that enhance employee satisfaction and motivation, thereby maintaining excellent service standards.